Pelatihan Peningkatan Keterampilan Komunikasi Interpersonal Pada Anak Panti Asuhan Cahaya Natanael Medan - Weny, Weny; Sulaiman, Fahmi (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Interpersonal communication skills are essential competencies for children in orphanages to build self-confidence and social adaptability. This community service project aims to enhance the interpersonal communication skills of children at the Cahaya Natanael Orphanage in Medan through the Role Play Project method. The participants consisted of 33 children from diverse regional backgrounds, aged between 6 and 18 years. The implementation methods included delivering basic communication theories, role-play simulations based on daily case studies, and participatory observation. Data were collected through field notes and analyzed using a qualitative approach. The results indicated an increased awareness of the importance of communication; however, the training objectives were not fully achieved across all participants. A significant variation in success was observed, where children who had resided longer and knew each other well were able to coordinate effectively, whereas new residents and those still grieving the loss of their parents tended to face obstacles in initiating interactions. The role of authority figures, such as the orphanage matron, remained dominant in directing the children's communication. The conclusion of this service emphasizes the need for program sustainability through various routine activities at the orphanage and consistent daily evaluations. Key recommendations include strengthening feedback mechanisms from the children and integrating communication exercises into every celebration at the orphanage to accelerate the children's social adaptation process.